Training for museums and the National Charter for museum professions in Italy: a new prospective for development (Cadernos de Sociomuseologia, 2012)
Traditionally Italian universities have trained researchers and professionals in conservation: archaeologists, art historians and architects. It is only with the reform of the universities, from 1999, that the teaching of museology and museography have also been expanded.Italian museums are for the most part public museums, depending on local bodies or the national ministry; they lack autonomy and do not possess specific professional figures. The task of conservation has predominated over the other roles of museums, but with the reform of the conservation law in 2004 the definition of „museum‟ has been introduced in Italy as well, and regulations regarding the development of heritage have been issued; in addition the Regions have also taken on a more active role for museums belonging to local bodies and for the development of their territory.Museum professions are not officially recognised, but the museum community, through the various associations and ICOM Italia, has put together a document to act as a general reference, the National Charter of Museum Professions, which has been followed by the Manual of Museum Professions in Europe.Now there is a need to plan the content and outlines ofvocational training courses for museum professionals, together withthe universities, the regions and the museums themselves, alongwith the associations and ICOM – ICTOP, utilising the mostinnovative Master‟s courses which offer an interdisciplinaryapproach, a methodology which combines theory and practice, andan element of hands-on experimentation in museums, or withmuseums.